Evaluation of candidate genes related to litter traits in Indian pig breeds. Issue 4 (2nd February 2021) - Vashi, Yoya; Magotra, Ankit; Kalita, Dipjyoti; Banik, Santanu; Sahoo, Nihar R.; Gupta, Sanjay K.; Naskar, Soumen
Abstract: Improvement in litter traits is the key to profitable pig farming that directly enhances the economic standing of the farmers in developing countries. The present study aimed to explore oestrogen receptor ( ESR ), epidermal growth factor ( EGF ), follicle‐stimulating hormone beta subunit ( FSHβ ), prolactin receptor ( PRLR ) and retinol‐binding protein 4 ( RBP4 ) genes as possible candidate genetic markers for litter traits in indigenous pigs of India. The breeds included in the study were Ghungroo, Mali, Niang Megha and Tenyi Vo, and the reproductive traits considered were litter size at birth (LSB), number born alive (NBA), litter weight at birth (LWB), litter size at weaning (LSW) and litter weight at weaning (LWW) at their first parity. PCR‐RFLP and primer‐based mutation detection methods were used to identify polymorphism, and associations between the genotypes and the traits were analysed using a general linear model. The Ghungroo pigs recorded the best litter performances among the breeds ( p < .05, LWB p < .01). Different alleles and genotypes of the genes under study were detected. Short interspersed nuclear element (SINE) −/− genotype of FSHβ revealed significantly higher litter traits ( p < .05, LSB p < .01). The LWW was also found to be significantly influenced by ESR BB and AB, EGF AB and BB, and PRLR CC genotypes ( p < .05). Although we did not find statistically significant and consistently superior litter traits with respect to different genotypes of other studied genes than genotype SINE −/− of the FSHβ, PRLR CC genotype demonstrated superior performances for all the litter traits. Our study revealed the FSHβ as a potential candidate genetic marker for litter traits in indigenous pig breeds of India.